Ulis students’ stereotypes of japanese people and responses from japanese exchange students = Hình ảnh khuôn mẫu về con người nhật trong nhận định của học sinh ulis và phản hồi từ du học sinh nhật - Đỗ, Như Quỳnh (2021)
The globalization in many recent decades has boosted the international cooperations between many countries and territories, thereby generating higher demand for crosscultural understandings. For that purpose, many studies have been conducted underneath this topic with the aim of increasing the cultural knowledge of every country to each other as well as minimizing the misunderstandings in the diplomatic affairs. The birth of this research about stereotypes could also be with that purpose under the situation that the relationship between Japan and Vietnam are undergoing higher level of cooperation and development. The researcher aimed at investigating the perceptions of ULIS students to Japanese people, then asked several Japanese exchange students to check whether those stereotypes reflect the true characteristics of Japanese people or not, thereby perceiving a more general look on Vietnam-Japan affairs as well as supplementing a source of crosscultural knowledge for the stakeholders. This study adopted the Qualitative Reseach Methodology in twelve subjects in which eight of them were students from ULIS and the rest were Japanese exchange students in Hanoi. The researcher collected data through semi-structured interviews with the aim of finding out the image of Japanese people in the perception of ULIS students and the responses to that image from Japanese exchange students.